2018
DOI: 10.1186/s12909-018-1400-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between learning styles and academic performance in TURKISH physiotherapy students

Abstract: BackgroundLearning style refers to the unique ways an individual processes and retains new information and skills. In this study, we aimed to identify the learning styles of Turkish physiotherapy students and investigate the relationship between academic performance and learning style subscale scores in order to determine whether the learning styles of physiotherapy students could influence academic performance.MethodsThe learning styles of 184 physiotherapy students were determined using the Grasha-Riechmann … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 23 publications
1
53
0
3
Order By: Relevance
“…Therefore, academic achievement among ATBU Bauchi students can be enhanced significantly when students employ efficient Study Strategies. Thus, the assertion of Jason et al (2018)'s findings, that high-achieving students endorse Study Strategies that have been demonstrated through empirical Ilcin et al (2018) and Zhou et al (2016) which revealed that academic performance of students was significantly associated with their learning style. Although there are quite different Study Strategies, the result in this study suggests that good Study Strategies significantly influences academic achievement of undergraduate students.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, academic achievement among ATBU Bauchi students can be enhanced significantly when students employ efficient Study Strategies. Thus, the assertion of Jason et al (2018)'s findings, that high-achieving students endorse Study Strategies that have been demonstrated through empirical Ilcin et al (2018) and Zhou et al (2016) which revealed that academic performance of students was significantly associated with their learning style. Although there are quite different Study Strategies, the result in this study suggests that good Study Strategies significantly influences academic achievement of undergraduate students.…”
Section: Discussionmentioning
confidence: 94%
“…Although Turkish physiotherapy students most commonly exhibited a collaborative learning style, the participant learning style was associated with significantly higher academic performance. However, Ilcin et al (2018)'s study was conducted on study strategy and academic performance which is the interest of the current study but his study was conducted in Turkish with physiotherapy student and the present study was conducted with general undergraduate students of ATBU Bauchi. Charles and Harriett (2017) in another study explored the motivational beliefs and learning strategy used by Liberia junior and senior school students in connection with their academic performance.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…The knowledge of learning styles grants pedagogical approaches and would provide imperative insights for students and teachers regarding either their strengths or their weaknesses in both teaching and learning practice [1,5]. The impact of learning style on academic performance of students has been previously veri ed in studies [6][7][8][9][10]. Several learning-style frameworks have been employed in different health science educational disciplines [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Também percebeu-se, no estudo, o predomínio de graduandos já inseridos no mercado de trabalho. Este perfil de estudantes foi semelhante ao encontrado em outros estudos conduzidos com graduandos em enfermagem e fisioterapia (MELO et al, 2017;PEREIRA et al, 2018;İlÇIN et al, 2018).…”
Section: Discussionunclassified